Pencarian Kandidat Vaksin Tbc Dari Epitope Protein Agj16802.1 (Virulence Factor Mce Family Protein [Mycobacterium Tuberculosis Str. Beijing/Nitr203]) - Prasetyaningtyas, Herawati Dwi; Wahjudi, Mariana; Yulanda Antonius (Syntax Literate, 2025)
In 2022, the burden of TB in the world was 10,556,328. The incidence of tuberculosis in Indonesia in 2021 was 969,000. The increase in TB incidence in 2021 was 18%. WHO has set a global target and milestone to reduce the incidence of TB by the end of 2030, as well as the Indonesian Ministry of Health. TB can be prevented with the BCG vaccine. BCG avoids phagosome maturation, autophagy, and reduces MHC-II expression of APCs that affect T cell activation by triggering an IgM antibody response, class-switched IgG, to specific proteins ESAT6 and CFP10. Protein subunit vaccines are an option to induce an immune response. Antigens recognized by cells during latent infection and involved in immunological evasion mechanisms or the emergence of CD4+ and CD8+ specific T cells are potential targets. One of these approaches is the incorporation of molecules capable of interacting with PRRs to recognize PAMPs. TLR is found in APC. The recognition of PAMPs by TLRs can result in the expression of co-stimulation molecules as well as the expression of proinflammatory cytokines, TNF-α, COX-2, and interferon associated with the development of adaptive immune responses by B and T lymphocytes. This project aims to determine the possibility of epitopes from protein AGJ68032.1 to be TB vaccine by comparing the results of docking epitope-TLR2 with TLR2-ESAT6. The material used in this project is protein AGJ68032.1 virulence factor Mce family protein [Mycobacterium tuberculosis str. Beijing/NITR203]. The steps were carried out: search for fasta AGJ68032.1, protein similarity test against Mycobacterium tuberculosis protein, determine the location of proteins, search for protein characteristics, find the location of all proteins, search for Bcell epitope, search for Tcell epitope (MHC class 2), epitope similarity test from MHC class 2 with homo sapiens, antigenecity test, allergenicity test, search for the 3D shape of each epitope-TLR2-ESAT-6, molecular docking TLR2 with ESAT-6 and TLR 2 with epitope and comparing the result data Docking. Epitope protein AGJ68031.1 (FAGDDVRIRGVPVGKIVKIEPQPLRAKVSFW) has high potential to be used as a tuberculosis vaccine candidate because the docking results with TLR have a HADDOCK score of -152.5 +/- 7.3 and an RSMD value that is close to the HADDOCK score and the RSMD TLR2 value with ESAT6.